Durable Antibacterial and Nonfouling Cotton Textiles with Enhanced Comfort via Zwitterionic Sulfopropylbetaine Coating. Issue 26 (23rd May 2016) - Chen, Shiguo; Yuan, Lingjun; Li, Qingqing; Li, Jianna; Zhu, Xingli; Jiang, Yongguang; Sha, Ou; Yang, Xinhui; Xin, John H.; Wang, Jiangxin; Stadler, Florian J.; Huang, Peng
Abstract : A rapid, environment‐friendly, and cost‐effective finishing method has been developed for cotton textiles by using zwitterionic NCO‐sulfopropylbetaine as the antibacterial finishing agent through covalent bond. The sulfopropylbetaine‐finished cotton textile exhibits durable broad‐spectrum antibacterial and nonfouling activity, improved mechanical properties, and enhanced comfort.